CONCEPT AND ESSENCE OF CREATIVE TASKS IN PEDAGOGICAL ACTIVITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the concept and essence of creative tasks in pedagogical activity. Comprehensive creative approach to teacher's activity, problem education, problem situations, system of problem teaching methods are enlightened.